Morphometric analysis of the mandibular canal using orthopantomogram : a comparison between dentate and edentulous patients - Mohamed Zauri, Aimi Suhaili; Abul Fatah, Farah Adila; Aung, Htar Htar (Anatomy Association of Thailand, 2013)
Objectives: The purpose of this study is to determine the diameter of mandibular canal (MC)and the distance between MC and upper and lower border of mandible in denate and edentulous patients. Materials and methods: A retrospective cross-sectional study was done on 150 OPGs of Malay and Chinese patients aged 20 and above taken at the Kulliyyah of Dentistry, IIUM. The measurements were conducted by using Planmeca Romexis Software. The data analysis was done with SPSS 20. Results: The mean (SD)vertical diameter of MC at mandibula foramen (MF) in dentate and edentulous patients was 4.18 (0.06)mm and 2.52 (0.09) mm respectivly, and when proximal to 3rd molar tooth were 3.25 (0.04)mm and 2.15 (0.06)mm. These differences were statistically signiicant. The diameter was slightly increased in male than female but it was not the statistically significant. The mean (SD)distance between MF and anterior border of ramus of mandibl was 13.72 (0.17) mm in dentate patients while for edentulous patients was 15.64 (2.29)mm. The distance decreased in aged >50 years and was statistically significant. The mean (SD)distance between MC nd alveolar crest in dentate and edentulous patient were 11.38 (0.18)mm and 7.64(0.39)mm. It was statistically significant. The distance was slightly decreased in Chinese and femae but these differences were not statistically different. In dentate patients, the mean (SD) distance between MF and posterior border of ramus of mandible was 14.13 (0.26)mm and in edentulous patient was 0.71 (0.30)mm.It was statistically significant. The mean (SD)distance between MC and inferior border of mandible in dentate and edentulous patient were 8.14 (0.14)mm and 7.11(0.30)mm. It was also statistically significant. Conclusion: Diameter of MC and distance between MC nad lower border of mandible were decrease in dentulous patients compared to dentate patients.